Epidemiological Features of Combined Natural-Focal Infections - V. V. Shkarin; A. S. Blagonravova; E. M. Chumakov (Эпидемиология и вакцинопрофилактика)
On the basis of literature data and results of own research in the article describes the features of the epidemiology of combined natural focal infections, their distribution in the Russian Federation, pathogenesis and clinical features to suit different combinations of pathogen agents. The data on the mixed infection of ticks by different agents in various combinations, as well as polyetiology infected of reservoir hosts Showing different variants of combined natural focal infections in humans caused by the associations of microorganisms, including up to five assiociants, as well as features of the pathogenesis and clinical manifestations Based on original research developed a method of a quantitative estimation the activity of combined natural foci and complex of measures on surveillance and control of combined natural focal infections.